A universal molecular control for DNA, mRNA and protein expression - Gunter, Helen M.; Youlten, Scott E.; Reis, Andre L. M.; McCubbin, Tim; Madala, Bindu Swapna; Wong, Ted; Stevanovski, Igor; Cipponi, Arcadi; Deveson, Ira W.; Santini, Nadia S.; Kummerfeld, Sarah; Croucher, Peter I.; et al. (Nature communications, 2024)
The expression of genes encompasses their transcription into mRNA followed by translation into protein. In recent years, next-generation sequencing and mass spectrometry methods have profiled DNA, RNA and protein abundance in cells. However, there are currently no reference standards that are compatible across these genomic, transcriptomic and proteomic methods, and provide an integrated measure of gene expression. Here, we use synthetic biology principles to engineer a multi-omics control, termed pREF , that can act as a universal molecular standard for next-generation sequencing and mass spectrometry methods. The pREF sequence encodes 21 synthetic genes that can be in vitro transcribed into spike-in mRNA controls, and in vitro translated to generate matched protein controls. The synthetic genes provide qualitative controls that can measure sensitivity and quantitative accuracy of DNA, RNA and peptide detection. We demonstrate the use of pREF in metagenome DNA sequencing and RNA sequencing experiments and evaluate the quantification of proteins using mass spectrometry. Unlike previous spike-in controls, pREF can be independently propagated and the synthetic mRNA and protein controls can be sustainably prepared by recipient laboratories using common molecular biology techniques. Together, this provides a universal synthetic standard able to integrate genomic, transcriptomic and proteomic methods. Multi-omics analyses powerfully combine gene expression and translation, however no available controls can be used across these techniques. Here the authors develop pREF, a universal control construct designed for use in DNA, RNA and protein analyses.